2016
DOI: 10.1177/0271678x16650455
|View full text |Cite
|
Sign up to set email alerts
|

Partial white and grey matter protection with prolonged infusion of recombinant human erythropoietin after asphyxia in preterm fetal sheep

Abstract: Perinatal asphyxia in preterm infants remains a significant contributor to abnormal long-term neurodevelopmental outcomes. Recombinant human erythropoietin has potent non-haematopoietic neuroprotective properties, but there is limited evidence for protection in the preterm brain. Preterm (0.7 gestation) fetal sheep received sham asphyxia (sham occlusion) or asphyxia induced by umbilical cord occlusion for 25 min, followed by an intravenous infusion of vehicle (occlusion-vehicle) or recombinant human erythropoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Our findings suggest that the amplified proinflammatory cytokine response to VIBI observed previously is likely due to the high dose (5,000 IU/kg) used or may be due to the timing of administration. High-dose EPO has been demonstrated previously to be neuroprotective in preterm lamb models of endotoxin-induced brain injury [35] and asphyxia [36] . Ventilation of preterm lambs with a high V T injurious ventilation strategy produces diffuse white matter injury [5] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings suggest that the amplified proinflammatory cytokine response to VIBI observed previously is likely due to the high dose (5,000 IU/kg) used or may be due to the timing of administration. High-dose EPO has been demonstrated previously to be neuroprotective in preterm lamb models of endotoxin-induced brain injury [35] and asphyxia [36] . Ventilation of preterm lambs with a high V T injurious ventilation strategy produces diffuse white matter injury [5] .…”
Section: Discussionmentioning
confidence: 95%
“…We have only investigated gene expression because of the acute nature of our protocol; further studies with longer durations are required to accurately determine whether increased cell death marker gene expression correlates with functional protein changes and apoptosis. A recent study which administered a bolus dose (5,000 IU) of EPO after asphyxia followed by 72 h of continuous infusion (832.5 IU/h) has demonstrated a reduced number of activated caspase-3-positive cells in preterm fetal sheep [36] .…”
Section: Discussionmentioning
confidence: 99%
“…; Wassink et al . ). Diffuse white matter injury evolves over time involving degenerative, proliferative and arrested maturation processes.…”
Section: The Global Burden Of Hypoxic–ischaemic Brain Injurymentioning
confidence: 97%
“…Multiple experimental studies have reported rEpo‐mediated neuroprotection with improved long‐term outcomes after HI (as reviewed by Wu & Gonzalez, ). For example, in preterm fetal sheep, rEpo infusion from 30 min until 72 h after asphyxia improved neuronal and oligodendroglial loss, and electrophysiological restoration (Wassink et al . 2017).…”
Section: The Mechanisms Of Hypothermic Neuroprotectionmentioning
confidence: 99%